A cross sectional study of 100 athletes with jumper's knee managed conservatively and surgically. The Victorian Institute of Sport Tendon Study Group. Issue 4 (December 1997) - Cook, J L; Khan, K M; Harcourt, P R; Grant, M; Young, D A; Bonar, S F
Abstract : OBJECTIVES: Jumper's knee causes significant morbidity in athletes of all standards. However, there are few reference data on the clinical course of this condition in a large number of patients, and the aim of this study was to rectify this. METHODS: A retrospective study of the course of jumper's knee in 100 athletes who presented to a sports medicine clinic over a nine year period was carried out. Subjects completed a questionnaire designed to collect details of sport participation, symptoms, and time out of sport. Ultrasonographic results were recorded from the radiologists' reports. Histopathological results were obtained for patients who had surgery. RESULTS: Forty eight subjects recalled that symptoms of jumper's knee began before the age of 20 years. Symptoms prevented 33 from participating in sport for more than six months, and 18 of these were sidelined for more than 12 months. Forty nine of the subjects had two or more separate episodes of symptoms. Ultrasonography showed a characteristics hypoechoic region at the junction of the inferior pole of the patella and the deep surface of the patellar tendon. Histopathological examination showed separation and disruption of collagen fibres on polarisation light microscopy and an increase in mucoid ground substance consistent with damage of tendon collagen without inflammation. CONCLUSIONS: Jumper's knee has the potential to be a debilitating condition for a sports person. About 33% of athletes presenting to a sports medicine clinic with jumper's knee were unable to return to sport for more than six months.